Acrylonitrile–butadiene–styrene/poly(vinyl acetate)/nanosilica mixed matrix membrane for He/CH4 separation. Issue 5 (20th February 2014) - Bandehali, Samaneh; Kargari, Ali; Moghadassi, Abdolreza; Saneepur, Hamidreza; Ghanbari, Davood
ABSTRACT In the present work, the separation of He/CH4 through different polymeric membranes has been considered. In this regard, composite flat sheet membranes are prepared from blending acrylonitrile–butadiene–styrene (ABS) with different amounts of poly(vinyl acetate) (PVAc) (0–40 wt%). Gas permeability/selectivity analyses as well as the pressure effects were studied for the prepared membranes. The results demonstrated that the ABS/PVAc (20 wt%) membrane revealed higher permselectivity. Afterwards, novel mixed matrix membranes were prepared by incorporating 1–5 wt% SiO2 nanoparticles into the ABS/PVAc (20 wt%). Additionally, further modification was carried out with the addition of styrene–butadiene–rubber (SBR) (5–15 wt%). The primary results of the prepared mixed matrix membranes showed a significant increase in the He permeability together with a decrease in He/CH4 selectivity by incorporating the SiO2 nanoparticles into the blend membranes. Finally, with the introduction of SBR, the (He permeability) selectivity was enhanced from (6.30 Barrer) 45 for the neat ABS/PVAc (20 wt%) to (42.39 Barrer) 51.88 for the ABS/PVAc (20 wt%)/SiO2 (3 wt%)/SBR (15 wt%) membrane. © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.